Creation of 3D Volume Loss Mask and Mean Performance Analysis on 3d MR Images - Özic, Muhammet Üsame; Ekmekci, Ahmet Hakan; Özşen, Seral (British Journal of Healthcare and Medical Research, 2017)
Examination of changes in the brain during disease progression using numerical methods is one of the current topics investigated by neuroscience. One of the numerical methods developed for locally or globally analyzing changes in the brain is voxel based morphometry. With voxel based morphometry, volume differences between the intra and intergroup Magnetic Resonance images can be examined. The general voxel based morphometry studies performed in the literature are only mapped. However, tissue analysis and artificial intelligence studies using voxel based morphometry are inadequate. In this study, voxel based morphometry was used to create a three dimensional volume loss mask for Alzheimer's disease to use tissue analysis and artificial intelligence in the future studies. Two different masks were created for according to the usage of family wise error. Volume loss regions are cut from normalized segmented and smoothed normalized segmented gray matter images with the generated masks. The average values of the voxel values in these regions are statistically compared for four different scenarios. As a result of the comparison, segmentation made with normalized segmented and family wise error values have been more meaningful results than the other three scenarios.